A conceptual framework for smart production planning and control in Industry 4.0. (November 2022) - Cañas, Héctor; Mula, Josefa; Campuzano-Bolarín, Francisco; Poler, Raul
Highlights: To address the main concepts of production planning and control (PPC) systems. To review reference architectures for PPC. To identify the impact of Industry 4.0 technologies on a smart PPC system. To propose a conceptual framework of a smart PPC system dubbed as SPPC4.0. Abstract: This article aims to introduce the challenge (i.e., integration of new collaborative models and tools) posed by the automation and collaboration of industrial processes in Industry 4.0 (I4.0) smart factories. Small- and medium-sized enterprises (SMEs) are particularly confronted with new technological and organisational changes, but a conceptual framework for production planning and control (PPC) systems in the I4.0 context is lacking. The main contributions of this article are to: (i) identify the functions making up traditional PPC and smart production planning and control in I4.0 (SPPC 4.0); (ii) analyse the impact of I4.0 technologies on PPC systems; (iii) propose a conceptual framework that provides the systematic structuring of how a PPC system operates in the I4.0 context, dubbed SPPC 4.0. Thus SPPC 4.0 is proposed by adopting the axes of the RAMI 4.0 reference architecture model, which compiles and contains the main concepts of PPC systems and I4.0. It also provides the technical description, organisation and understanding of each aspect, which can provide a guide for academic research and industrial practitioners to transform PPC systems towards I4.0 implementations. Finally, theoretical implications and research gaps are provided.